Uji Aktivitas Analgesik Dari Ekstrak Daun Ara Sungsang (Asystasia gangetica L.) Terhadap Mencit Jantan dengan Metode Hot Plate - Fujiko, Muflihah; Saputri, Muharni; Sofia, Vivi; Mauliza, Indah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Pain is a body response that indicates a disorder. The use of conventional drugs to treat pain is quite worrying because of its long-term effects. This causes people to use drugs derived from nature. Breech fig leaves contain flavonoids and alkaloids that are able to reduce pain. This study aims to see the potential of breech fig leaves as an analgesic induced to male mice using the hot plate method. This research began with plant identification, material collection, simplicia and extract, phytochemical screening, and testing on mice. This study was carried out in vivo using male mice. Twenty birds were divided into five groups, namely the negative control group (CMC-Na 0.5%), the positive control group (Ibuprofen 200 mg/kg BB), the breech fig leaf extract group (dosage 50 mg/kg BB, 100 mg/kg BB, 200 mg/kg BB). Then the analgesic activity test was carried out by looking at the responsse of mice who were given pain using the hot plate method with a temperature of 55ºC. Then the percent of analgesic power and percent of the effectiveness of the analgesic were calculated. The results of the study showed that flavonoid compounds, alkaloids, tannins, steroids, and saponins were contained in breech fig leaves (Asystasia gangetica L.). dose 200 mg/kg BB has the highest percent analgesic power and effectiveness percentage, which is 99.12% (p<0,05) and 99.67% (p<0,05). From dose 50 mg/kg BB, the analgesic effect can be seen, and the best analgesic effect is at a dose of 200 mg/kg BB. This shows that breech fig leaf extract has analgesic activity in male mice by hot plate method.